Concentración de vitaminas liposolubles y antioxidantes de un cv tetraploide de Lolium multiflorum en dos cortes - Montenegro, Luciano Federico; Perez, Carolina Daiana; Garcia, Pilar Tere; Olivera, María Elena; Postulka, Elena B. (2022)
One of the most cultivated forage species is the annual ryegrass (Lolium multiflorum Lam). One of the parameters that define quality, often poorly studied, are fat-soluble vitamins and antioxidant pigments. These compounds are found in forage species and are assimilated by the animals that consume them, generating beneficial effects on their organism. However, the concentration of these vitamins and pigments varies throughout the growth cycle. For this reason, it is necessary to study the seasonal variation of vitamins in order to estimate the amount available to animals. The objective of this trial was to determine the variation in the concentration of fat-soluble vitamins and antioxidants at two moments during the growth cycle of a tetraploid cultivar of Lolium multiflorum Lam. It was possible to determine that the Bill Max tetraploid cultivar of Lolium multiflorum Lam. It has a high supply of fat-soluble vitamins and antioxidants that decrease significantly as the growing season progresses. This could be used to design grazing strategies in which the concentration of these compounds is taken advantage of at the times when they are in higher concentration.